Solving an Integral Equation via Orthogonal Branciari Metric Spaces - Aiman Mukheimer; Arul Joseph Gnanaprakasam; Absar Ul Haq; Senthil Kumar Prakasam; Gunaseelan Mani; Imran Abbas Baloch (Journal of Function Spaces)
In this article, we present an orthogonal L-contraction mapping concepts and prove a fixed point theorem on orthogonal complete Branciari metric spaces. As an application, we apply our major results to solving integral equations.